2022
DOI: 10.1123/ijspp.2021-0554
|View full text |Cite
|
Sign up to set email alerts
|

Power Road-Derived Physical Performance Parameters in Junior, Under-23, and Professional Road Cycling Climbers

Abstract: Purpose: To investigate the relationship of field-derived power and physical performance parameters with competition success in road cycling climbing specialists of age-related categories and to explore cross-sectional differences between high-ranked (HIGHR) climbing specialists of each category. Methods: Fifty-three male climbers participated in this study (junior [JUN], n = 15; under 23 [U23], n = 21; professional [PRO], n = 17). Training and racing data collected during the 2016–19 competitive seasons were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Despite spending more energy before the 5-min test, both seniors and U23 performed better than juniors in absolute power output, with a similar trend found for mean power output expressed relatively to body mass (age-group P = 0.055). This indicates an improved durability with age, which is in line with field-derived power data on development of outdoor performance from junior cyclists to professionals (40). The common improvements in performance level as a cyclist matures seem to be related to improved durability, which can be detected already after ~15–20 kJ·kg −1 of energy spent when using a highly standardized laboratory setting.…”
Section: Discussionsupporting
confidence: 84%
“…Despite spending more energy before the 5-min test, both seniors and U23 performed better than juniors in absolute power output, with a similar trend found for mean power output expressed relatively to body mass (age-group P = 0.055). This indicates an improved durability with age, which is in line with field-derived power data on development of outdoor performance from junior cyclists to professionals (40). The common improvements in performance level as a cyclist matures seem to be related to improved durability, which can be detected already after ~15–20 kJ·kg −1 of energy spent when using a highly standardized laboratory setting.…”
Section: Discussionsupporting
confidence: 84%
“…Field data from elite cyclists indicate that resilience may continue to increase up to the highest levels, with even more extensive and long-term exposure to endurance training. 17 On the lower end of the scale, the magnitude and type of training required to induce improvements in physiological resilience have yet to be explored, beyond the fact that the training exposure of TR in the current study appears to be sufficient to improve resilience.…”
Section: Determinants Of Physiological Resiliencementioning
confidence: 92%
“…On the other hand, field data from elite cycling suggests that the ability to produce high wattage in a fatigued state is a characteristic that separates professional road cyclists from elite under 23 and junior cyclists. 17 The purpose of the present study was therefore to investigate whether the ability to resist changes in VO 2max and RE is different between trained and untrained runners, when tested before and after 1 h of running at 70% of VO 2max . Specifically, we hypothesized that (1) the ability to resist changes in RE would be superior in trained versus untrained runners, and (2) the ability to resist changes in VO 2max would be superior in trained versus untrained runners.…”
Section: Introductionmentioning
confidence: 98%
“…In the last years, there has been a rapid increase in the capacity to capture real-time data through portable mechanical power meters. This has led to a deeper understanding of both race demands [2][3][4] and parameters associated with competition outcomes in road cycling 4,5 . However, there is a paucity of study reporting training characteristics of professional road cyclists with only few studies reporting the professional cyclists training data as a mean of the sample considered [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a deeper understanding of both race demands 2 , 3 , 4 and parameters associated with competition outcomes in road cycling. 4 , 5 However, there is a paucity of study reporting training characteristics of professional road cyclists with only few studies reporting the professional cyclists training data as a mean of the sample considered. 6 , 7 , 8 To the best of our knowledge, no study has reported the individual day‐to‐day training and racing data of world‐class road cyclists preceding an important competition, as it has already been done in recent studies in world class endurance athletes.…”
Section: Introductionmentioning
confidence: 99%